Analysis Of Youth Language And Taboo Words In the Gayo Language - Muhammad Hasyimsyah Batubara; Vera Ramayana; Cut Dara Ilfa Rahila (Asosiasi Dosen Perguruan Tinggi Islam, 2022)
This study is about taboo words spoken by the younger generation in Takengon. In this study, researchers carried out three activities: data collection activities, data analysis, and presentation of the analysis results. The data collection method used in this study is the listening method with the free engagement speaking technique. Furthermore, data analysis was carried out using the extra lingual equivalent method, which emphasized the determining tool on Gayo sumang or taboo words in the Gayo language spoken by young speakers in the Takengon area. The data analysis results are presented using an informal or narrative method. For the taboo words spoken by the current generation, such as Ulumu, Jalang Nine E, Fakalaya, Nantak, Benatang, Lelang, Senare Kurang Sengkal, and Tenek. Based on these findings, it is hoped that the people of Central Aceh District can understand the word taboo contained in sumang perceraken so that people can communicate and speak good words because it is part of the customary values in sumang Gayo.